FAKTOR TIDAK LANGSUNG DENGAN KEJADIAN GIZI KURANG DAN BURUK PADA BALITA DI WILAYAH KERJA PUSKESMAS KUTABUMI KABUPATEN TANGERANG - Nuraliyani Nuraliyani; Epa Yohanta (Jurnal Kesehatan, 2018)
Nutrition issues are incorporated into Millennium Development Goals (MDGs) with the first goal of addressing malnutrition, improving child health and reducing child mortality where one of the factors is caused by malnutrition. To identify indirect factors related to the incidence of malnutrition in children under the age of five in the working area of Kutabumi Community Health Center of Tangerang Regency. Research method of Correlative descriptive research with cross sectional approach. Population in this research is all of mother all under five in working area of Kutabumi Public Health Center of Tangerang Regency. Samples in research ii as many as 198 mother of kids taken by purposive sampling technique. Data obtained by distributing questionnaires that have been valid and reliable. Univariate and bivariate data analysis using chi-square test for categorical data and person correlation for numerical data. From 198 respondents, the average age was 31.67 years old, based on the level of education most of the respondents were secondary education (SMA / SMK) as many as 110 respondents (55.6%) and 120 respondents (60.6%) with number of children little (≤ 2 children). Of the 198 respondents most of the good nutrition that is 114 respondents (57.6%), there are 66 (33.3%) malnutrition and 18 (9,1%) malnutrition, not good enough that 116 respondents (58,6% (p = 0.042), the number of children (pvalue = 0.002), the number of children (pvalue = 0,002), the number of children (pvalue = 0,002) knowledge (pvalue = 0,000), family income (pvalue = 0,000) and parenting (pvalue = 0,000) with less and less nutritional incidence in infants. There is no correlation between maternal age and the incidence of malnutrition in children under five (Pvalue = 0,056). There is a relationship between maternal education, the number of children, knowledge, family income and the pattern of care with the incidence of malnutrition in children under five. Puskesmas is recommended to make the results of research as a reference in composing astrategy of malnutrition